STUDY SYARAH SHAHIH AL-BUKHARI; AT-TAUDHIH LI SYARHI AL-JAMI’ ASH-SHAHIH IBN AL-MULAQQIN - M Mu’min (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2018)
This study discusses the Sahih Sahih Al-Bukhari At-Taudhih Li Syarhi Al-Jami Ash-Sahih Ibn Al-Mulaqin, using the historical approach and literature study (Research library). It was found that Syarah Ibn Al-Mulaqin was one of the very thick Sahih books of al-Bukhari, containing a lot of information, and was rich in approaches from various disciplines that were compiled for 22 years. The method used by Ibn Mulaqin is by explaining grammar, stretching the interrelationship of the subtitles with the title, then explaining the narrator and then discussing the contents of the hadith in detail, by explaining the history, the rijal of hadith, and Fiqh.